2020
DOI: 10.51135/publicpolicy.v1.i2.p195-214
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Good Coorporate Governance, Good Governance dan Kepemimpinan Situasional Terhadap Kinerja Pegawai

Abstract: This study aimed at finding out and analyzing the effect of good corporate governance, good governance and situational leadership on employees’ performance (a study at public hospital in Masohi region). The hypotheses formulated in this study were: 1) Good corporate governance had positive effects on employees’ performance at public hospital in Masohi; 2) Good governance had positive effects on employees’ performance at public hospital in Masohi; 3) Situational leadership had positive effects on employees’ per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
1
5
0
1
Order By: Relevance
“…Based on this, it can be concluded that the implementation of good governance plays a role or has an influence on employee performance. These research findings are consistent with previous studies conducted by [20]- [22] which concluded that the implementation of good governance has a positive impact on employee performance.…”
Section: Figure 3 Heteroscedasticity Test Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Based on this, it can be concluded that the implementation of good governance plays a role or has an influence on employee performance. These research findings are consistent with previous studies conducted by [20]- [22] which concluded that the implementation of good governance has a positive impact on employee performance.…”
Section: Figure 3 Heteroscedasticity Test Resultssupporting
confidence: 93%
“…Good governance emphasizes the importance of transparency in decision-making, accountability in task execution, employee participation in decision-making processes, fairness in resource distribution, and efficiency in resource utilization within the organization. Implementing these principles can have a positive impact on employee performance [22], [23].…”
Section: Good Governancementioning
confidence: 99%
See 1 more Smart Citation
“…Hasil penelitian menunjukkan kepemimpinan dan kecurangan berpengaruh negatif terhadap kecurangan yang berarti kepemimpinan yang dapat menurunkan terjadinya kecurangan. Berdasarkan teori pendekatan stasional ini menekankan karakteristik pribadi pemimpin dan situasi, menyarankan dan mencoba untuk mengukur atau memperkirakan karakteristik pribadi ini, dan membantu para pemimpin untuk memandu perilaku mereka (Watimena, 2020). Oleh Pendekatan situasional juga menekankan faktor kontekstual yang mempengaruhi proses kepemimpinan.…”
Section: Kepemimpinan Berpengaruh Terhadap Terjadinya Kecuranganunclassified
“…Professionalism here puts more emphasis on the ability, skills, and expertise of government officials in providing responsive, transparent, productive, and efficient public services. Watimena (2020) in his research also said that managers in companies have a role in regulating or controlling debt levels, issued by companies, so that they can improve company performance, this is also the same with tax service leaders and staff.…”
Section: Literature Referencesmentioning
confidence: 92%